Seleksi Burung Puyuh Generasi II Berdasarkan Bobot Badan dan Perubahan Biokimia Genetika - S M Ardiningsasi (Faculty of Animal Science, Bogor Agricultural University, 2007)
The birds were developed to be 16 groups (4 groups of TT and 4 groups of RR, with male and female lines, respectively). The mating was conducted between similar groups of population (TT vs. TT, and RR vs. RR) to obtain second generation. The change in metabolism such as Ca-ATPase activity and Nô-œmethylhistidine (Nô-MH), also selection response between generations were analyzed. Parameters of metabolism were subjected to statistical analysis of T-test to compare between productions characteristic (TT and RR), especially for second generation. Body weight was also statistically analyzed by the same method. Selection response in TT group (3.10% or 2.74%) was higher than that in RR group (1.20% or 1.13%). Metabolism aspect in the quails of second generation either rate of protein turnover or activity of bone Ca-ATPase enzyme showed the change toward the productivity specification. Rate of muscle protein synthesis was higher and enzyme activity of Ca-ATPase was lower in group of TT population than those in group of RR population. Key words: quail, breeding, body weight, protein turnover, Ca-ATPase